(untitled) (Journal of Oriental Studies, 2024)
Kashmir has been a cultural crossroads for centuries for different nationalities, languages, and religious communities. The geographical location of Kashmir, along with its rich ethnic mosaic with various cultural, religious, and linguistic characteristics, has led to the development of a unique landscape in which formal and informal institutions are closely intertwined. At present, political instability and conflict potential in the region have been added to the palette of ethnic and cultural diversity, which has led to increased militarization of the region. Against this backdrop, the research, by considering the characteristics of the historical and ethnic-cultural development of the Kashmiris, analyses the causes and mechanisms of the emergence and formation of informal institutions, as well as the nature of their sustainability in the current socio-political conditions. To achieve this, the article first examines the historical background and ethnic and cultural context of Kashmir. Then, it reveals the reasons for the conflict potential of the region and its consequences for the development of social ties. Further, using the cases of informal institutions, the article analyses how the local population uses the mechanisms of informal practices to solve various social issues, bypassing complex procedures in formal structures. In conclusion, the article reflects on the role of informal mechanisms in the context of the broader development of Kashmir. Keywords: Kashmir, informal institutions, cultural diversity, informal networks